Novel multi-field coupling high-voltage electric pulse fracturing coal–rock permeability enhancement test system. (October 2022) - Jia, Li; Peng, Shoujian; Xu, Jiang; Yan, Fazhi; Zhou, Jing; Chen, Jieren
Abstract: With the significant development of coal mining, complex coal reservoir environments with a high gas content, high stress, and low permeability increase the difficulty in efficient and large-scale extraction of gas. To further study the mechanism of coal–rock fracturing using a high-voltage electric pulse (HVEP) and to determine the influence of the HVEP on the permeability enhancement, a multi-field coupling HVEP fracturing coal–rock permeability enhancement test device was independently developed. The device mainly includes a servo loading and control system, high-voltage charging system, energy storage system, and data acquisition system. Considering the coupling effects of the electric field, in-situ stress field, and seepage field, this paper proposes the HVEP fracturing technology. The test device can provide an axial pressure of 50 MPa, confining pressure of 16 MPa, and seal gas pressure of 5 MPa with high insulation, which can simulate the permeability enhancement of deep coal–rock due to the application of an HVEP. The device realizes the real-time monitoring of voltage, current, in-situ stress, and gas flow during the HVEP fracturing of coal–rock. The experimental device was used to carry out an HVEP fracturing coal–rock permeability enhancement test. The dynamic response characteristics of the voltage, current, pore, fractures, and permeability during the coal–rock breakdown were analyzed. This study provides a novel laboratory physical simulation technology for the large-scale extraction of gas. Highlights: A multi-field coupling HVEP fracturing coal–rock permeability enhancement test device was developed. The cavity of coal–rock can exhibit a high insulation and bear an axial pressure of 50 MPa. The proposed device realizes the real time monitoring of voltage, current, in-situ stress, and gas flow.